2010
DOI: 10.1111/j.1574-6968.2010.02106.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the antimicrobial peptide microcin N

Abstract: Microcins are low-molecular-weight proteins secreted by certain bacteria that act by limiting the growth of other bacteria that share the same ecological niche. In the present work, the previous microcin 24 system was resequenced.We detected three nucleotide differences in the microcin-coding gene that partially change the amino acid sequence. According to the present microcin nomenclature, we renamed the five genes constituting this microcin system (mcnRINAB), which are arranged in an operon-like structure: m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
(42 reference statements)
1
25
0
2
Order By: Relevance
“…MccV, MccL and McnN are natively produced by E. coli while the remaining peptides are produced by Enterococcus , a Gram-positive genus of bacteria [17,19,23,32,33]. Like MccV, the studied enterocins are considered class II bacteriocins, which generally lack major post-translational modifications and are commonly secreted by ABC-transporters using N-terminal secretion tags [34].…”
Section: Resultsmentioning
confidence: 99%
“…MccV, MccL and McnN are natively produced by E. coli while the remaining peptides are produced by Enterococcus , a Gram-positive genus of bacteria [17,19,23,32,33]. Like MccV, the studied enterocins are considered class II bacteriocins, which generally lack major post-translational modifications and are commonly secreted by ABC-transporters using N-terminal secretion tags [34].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the NRPSs in gene cluster one revealed that this locus likely encodes proteins involved in the biosynthesis of a microcin (Table 2). SMA1574A shows 41 % identity with microcin N of E. coli 2424 (Corsini et al , 2010) and the NRPS proteins, SMA1572 and SMA1571, are likely involved in the biosynthesis of a modifying group added to the microcin peptide encoded by this gene cluster (Rebuffat, 2012). In contrast, gene clusters two and five appear to direct the synthesis of multiple siderophores (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…There are four known class IIa microcins, microcin V (MccV, previously named colicin V) (54, 55), microcin N (MccN, previously named Mcc24) (56), microcin L (MccL) (57), and microcin PDI (MccPDI) (58, 59). The operons encoding these microcins contain four or five genes, including the microcin precursor, immunity and export genes.…”
Section: Discussionmentioning
confidence: 99%
“…The operons encoding these microcins contain four or five genes, including the microcin precursor, immunity and export genes. MccN also encodes a putative regulator, with a histone-like nucleoid domain (56). The microcin precursor genes possess leader sequences of approximately 15 amino acids, containing the signature sequence MRXI/LX(9)GG/A (X=any amino acid), and are typically cleaved by the ABC transporters during export (60).…”
Section: Discussionmentioning
confidence: 99%